Atypical HELLP Syndrome in a Pregnant Patient with Takayasu Arteritis and Subclavian to Axillary Artery Saphenous Vein Bypass Graft: A Case Report - Hediye Dağdeviren; Hüseyin Cengiz; Sema Süzen Çaypınar; Cihan Kaya; Ammar Kanawati (Gynecology Obstetrics & Reproductive Medicine)
Takayasu arteritis (TA) is a rare chronic granulomatous inflammatory disease of the aorta and/or its major branches, affecting mostly the vertebral, carotid, subclavian, iliac, and renal arteries. The disease shows a striking predilection for women during the child-bearing years, and it is reasonable to expect at least 1 pregnancy event in these women. Therefore, the management of pregnancies in patients with this disease is of great importance to obstetricians. Here, we present the case of a patient with atypical hemolysis, elevated liver enzymes, and low platelets (HELLP syndrome); this patient was receiving corticosteroid therapy and had undergone subclavian-axillary artery saphenous vein graft for TA.